Frequency spectrum of the human head–neck to mechanical vibrations. Issue 3 (September 2018) - Yang, Bin; Shi, Zheng; Wang, Qun; Xiao, Feng; Gu, Tong-Tong; Yin, Yong-Kai; Miao, Zhong-Liang
This study is based on a real finite element human head–neck model and concentrates on its numerical vibration characteristic. Frequency spectrum and mode shapes of the finite element model of human head–neck under mechanical vibration have been calculated. These vibration characteristics are in good agreement with the previous studies. The simulated fundamental frequency of 35.25 Hz is fairly similar to the published documents, and rarely reported modal responses such as "mastication" and flipping of nasal lateral cartilages modes, however, are introduced by our three-dimensional modal analysis. These additional modes may be of interest to surgeons or clinicians who are specialized in temporomandibular or rhinoplasty joint disorder. Modal validation in terms of modal shapes proposes a necessity for elaborate modeling to identify each individual part's extra frequencies. Furthermore, it also studies the influence of damping on resonant frequencies and biomechanical responses. It is discovered that damping has an inverse proportionality between damping effect on natural frequency and that on biomechanical responses.